The role of copper in Wilson's disease: therapeutic strategies - Aguiar, Paula Filipa de Albuquerque Dinis Ferreira (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2020, Universidade de Lisboa, Faculdade de Farmácia.